Perancangan Animasi 3D “Rahmat Allah yang Terindah” dengan Menerapkan Metode Keyframe - Lailatul Fadilah; Juniardi Nur Fadila; Fresy Nugroho (Program Studi Sistem Informasi Fakultas Sains dan Teknologi, UIN Sunan Ampel Surabaya, 2021)
3D animation is one of the applications of computer graphics. 3D animated films can be used as learning media to convey messages. In its implementations, there are still many 3D animated films that produce stiff and unrealistic movements. This is because there are deficiencies in the animation process. This problem is the background of this research. The goal to be achieved is to find the right method to produce animated movements that are not rigid so that they can convey the message well. The theme of this is islamic and mother love. The method used in the animating process is the keyframe method; method of making 3D animation that starts from one point to another until it becomes a unified visualization of object images. The design of 3D animation is done using blender software and is carried out in 8 stages, namely determining story design, storyboarding, character modeling, texturing, rigging, animating, rendering, and editing. This research produces a mp4 formatted 3D animated film with a duration of 90 seconds. The keyframing method is also proven to be effective and easy to apply to produce smooth animation movements if the interpolated value is reduced.